Implementasi Autentikasi pada Protokol CoAP menggunakan Feige-Fiat-Shamir Identification Scheme - Julio Dimitri Fredrik; Ari Kusyanti; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Authentication is a problem in Constrained Application Protocol (CoAP). JSON Web Token is one of standard in authentication mechanisms. However, this method has vulnerability in unsecure connection. This is due JWT authentication mechanism send hash secret directly. Feige-Fiat-Shamir (FFS) Identification Scheme is an authentication method apply Zero-Knowledge Proof (ZKP) mechanism. ZKP mechanism is based on knowledge to proof secret without reveal single bit on the secret. This research starts by making pair of secret. The device in this research is hard code by the each one of the secret pair. Then, authentication mechanism is done by proving the that the pairs of secret is valid using FFS Identification Scheme. This research result that FFS Identification Scheme can be use on CoAP authentication. Duplication secret on authentication mechanism by sniffing can be resolve by FFS Identification Scheme mechanism. This research also provides memory and authentication performance enhancement up to 256 bits secret.